5,000 staf and students attended Aidil Fitri Celebration - UMP, PNC
Some 5,000 UMP staff and students attended the Aidil Fitri celebration graced by His Highness Sultan of Pahang, Sultan Haji Ahmad Shah Al-Musta’in Billah Ibni Almarhum Sultan Abu Bakar Ri’ayatuddin al-Muadzam Shah and Her Highness Sultanah of Pahang, Sultanah Hajah Kalsom.